2014
DOI: 10.1590/s0036-46652014000600001
|View full text |Cite
|
Sign up to set email alerts
|

PREVALENCE OF DRUG RESISTANCE AND VIRULENCE FEATURES IN Salmonella spp. ISOLATED FROM FOODS ASSOCIATED OR NOT WITH SALMONELLOSIS IN BRAZIL

Abstract: Salmonella is the most common etiological agent of cases and outbreaks of foodborne diarrheal illnesses. The emergence and spread of Salmonella spp., which has become multi-drug resistant and potentially more pathogenic, have increased the concern with this pathogen. In this study, 237 Salmonella spp., associated or not with foodborne salmonellosis in Brazil, belonging mainly to serotype Enteritidis, were tested for antimicrobial susceptibility and the presence of the virulence genes spvC, invA, sefA and pefA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 52 publications
5
24
0
5
Order By: Relevance
“…These genes were also screened by other researchers in meat, poultry and food samples (El Allaoui et al, 2013;Karmi, 2013;Rowlands et al, 2014) which are in substantial agreement with our findings.…”
Section: Molecular Detection Of Salmonella Enterica and Its Virulencesupporting
confidence: 92%
“…These genes were also screened by other researchers in meat, poultry and food samples (El Allaoui et al, 2013;Karmi, 2013;Rowlands et al, 2014) which are in substantial agreement with our findings.…”
Section: Molecular Detection Of Salmonella Enterica and Its Virulencesupporting
confidence: 92%
“…Non-typhoid Salmonella strains, including serotypes S. Anatum, S. Infantis, and S. Panama, can cause gastroenteritis, which can progress to systemic infections (bacteremias and meningitis) (Huang et al, 2013;Rowlands et al, 2014). These strains may display an invasive capacity, a characteristic of multi-resistance to antimicrobial drugs, which are genes encoded capacity that may potentiate their persistence in the organism and hence, their pathogenicity (Ribeiro et al, 2007;Huang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The detection of virulence-related genes showed that all 44 isolates were positive for invA (invasion), fimA and agfA (adherence), and sfbA (component of the iron transport system) genes and negative for spvC (motility) and fliC (adherence and invasion) genes. Only one isolate (231/2001) was negative for phoP/Q (intra-macrophage survival),while slyA (a virulenceassociated transcriptional regulator) was detected in 12 isolates obtained from food (7), estuarine water (2), and rectal swab from a lizard (3). Salmonella infections show multifactorial pathogenesis and that multiple virulence genes may be involved.…”
Section: No/yearmentioning
confidence: 99%
“…The ability of Salmonella spp. to cause disease can be attributed to an array of virulence genes located in the chromosomes or in large virulence-associated plasmids 3 . Several factors related to the virulence of Salmonella spp.…”
mentioning
confidence: 99%